Access to Pediatric Surgery Delivered by General Surgeons and Anesthesia Providers in Uganda: Results from 2 Rural Regional Hospitals - Grabski, David F.; Ajiko, Margaret; Kayima, Peter; Ruzgar, Nensi; Nyeko, David; Fitzgerald, Tamara N.; Langer, Monica; Cheung, Maija; Cigliano, Bruno; D’Agostino, Sergio; Baird, Robert; Duffy, Damian; et al. (Surgery, 2021)
Significant limitations in pediatric surgical capacity exist in low- and middle-income countries, especially in rural regions. Recent global children’s surgical guidelines suggest training and support of general surgeons in rural regional hospitals as an effective approach to increasing pediatric surgical capacity.Two years of a prospective clinical database of children’s surgery admissions at 2 regional referral hospitals in Uganda were reviewed. Primary outcomes included case volume and clinical outcomes of children at each hospital. Additionally, the disability-adjusted life-years averted by delivery of pediatric surgical services at these hospitals were calculated. Using a value of statistical life calculation, we also estimated the economic benefit of the pediatric surgical care currently being delivered. From 2016 to 2019, more than 300 surgical procedures were performed at each hospital per year. The majority of cases were standard general surgery cases including hernia repairs and intussusception as well as procedures for surgical infections and trauma. In-hospital mortality was 2.4% in Soroti and 1% in Lacor. Pediatric surgical capacity at these hospitals resulted in over 12,400 disability-adjusted life-years averted/year. This represents an estimated economic benefit of 10.2 million US dollars/year to the Ugandan society.This investigation demonstrates that lifesaving pediatric procedures are safely performed by general surgeons in Uganda. General surgeons who perform pediatric surgery significantly increase surgical access to rural regions of the country and add a large economic benefit to Ugandan society. Overall, the results of the study support increasing pediatric surgical capacity in rural areas of low- and middle-income countries through support and training of general surgeons and anesthesia providers.